Emissions of Airport Monitoring with Solar Occultation Flux-Fourier Transform Infrared Spectrometer - Xin Han; Xiangxian Li; Minguang Gao; Jingjing Tong; Xiuli Wei; Sheng Li; Shubin Ye; Yan Li (Journal of Spectroscopy)
Both domestic and international aviation industries have experienced a boom, which results in a dramatic increase in emissions of the aviation industry in recent decades. Therefore, domestic and abroad scientists adopted different methods to measure emissions; however, there are no appropriate methods to measure the emissions of the whole airport. In order to provide data support for the relevant departments to take appropriate emission reduction measures, solar occultation flux-Fourier transform infrared spectrometer (SOF-FT-IR) is used to monitor the emissions of Beijing Capital International Airport. CO, CO2, C2H4, and CH2O are selected as the target gases and are quantitatively analyzed with the nonlinear least squares method to get the column concentration. Then, the flux can also be calculated by linking the wind velocity and direction with the column concentration. A comparison between the results measured by SOF-FT-IR and the results measured by the method published by the Intergovernmental Panel on Climate Change (IPCC) indicates that auxiliary power equipment and ground support equipment for the emission of the airport are also important emission sources besides the aircraft and the concentration distribution gives powerful and useful pieces of evidence to locate the emission sources. In order to decrease the contribution of the airport to the air pollution, the key point is to reduce the emissions of the APU and mobiles in the airport.